2011
DOI: 10.3758/s13428-011-0061-4
|View full text |Cite
|
Sign up to set email alerts
|

A two-choice sound localization procedure for detecting lateralized tinnitus in animals

Abstract: Rats were trained in a two-choice procedure to respond in the direction of left and right sounds. Silent trials, on which no sound was presented and for which the animals received no feedback, were interspersed among the sound trials to determine each animal's natural side preference. Following training, the rats were exposed to a loud tone in the ear opposite their side preference. A shift in responding on the silent trials to the side of the exposed ear indicated that the animals were hearing a sound in that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
(42 reference statements)
1
19
0
Order By: Relevance
“…Accordingly, animals with tinnitus should switch their side preference during silent trials from the side preferred prior to noise exposure (the right side in the above example) to the opposite, noise-exposed side (the left side in the above example) because the animals now hear a phantom sound on that exposed side. In accordance with their hypothesis, the researchers found that hamsters (16) and rats (39) will shift their side preference on silent trials to the noise-exposed, previously non-preferred ear, suggesting that they perceive a phantom sound in that ear. As an important control condition, simply plugging one ear and producing a conductive hearing loss does not result in a shift in behavior on silent trials.…”
Section: Animal Models Of Tinnitussupporting
confidence: 58%
See 1 more Smart Citation
“…Accordingly, animals with tinnitus should switch their side preference during silent trials from the side preferred prior to noise exposure (the right side in the above example) to the opposite, noise-exposed side (the left side in the above example) because the animals now hear a phantom sound on that exposed side. In accordance with their hypothesis, the researchers found that hamsters (16) and rats (39) will shift their side preference on silent trials to the noise-exposed, previously non-preferred ear, suggesting that they perceive a phantom sound in that ear. As an important control condition, simply plugging one ear and producing a conductive hearing loss does not result in a shift in behavior on silent trials.…”
Section: Animal Models Of Tinnitussupporting
confidence: 58%
“…During the sound localization procedure, animals were trained to lateralize sounds by responding to the right side of a test box for sounds coming from a speaker on the right side and to respond to the left side of a test box for sounds coming from the left side (16, 39). Animals were given water reward for correct responses and were shocked for incorrect responses.…”
Section: Animal Models Of Tinnitusmentioning
confidence: 99%
“…In response to the need to find effective therapies for chronic tinnitus, several animal models were developed over the last 20 years and have been used to study drug-or noise-induced tinnitus (Jastreboff et al 1988a;Bauer et al 1999;Bauer and Brozoski 2001;Heffner and Harrington 2002;Guitton et al 2003;Ruttiger et al 2003;Lobarinas et al 2004;Heffner and Koay 2005;Lobarinas et al 2006;Turner et al 2006;Turner and Parrish 2008;Heffner 2011;Yang et al 2011). The animal models provide distinct advantages as (1) experiments with high-level noise exposures to induce tinnitus cannot be ethically carried out in humans, (2) tinnitus etiology is under the experimenter's control, and (3) preclinical trials are necessary to establish both safety and efficacy of novel compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The second established method for inducing tinnitus in behavioral models is through acoustic trauma [8, 15, 20, 21, 23, 2527, 30, 31, 37, 3942, 4649, 5156, 5966, 68, 69, 107]. It is assumed that a cochlear damage is in most cases the trigger for a sequence of events leading to the development of tinnitus in humans.…”
Section: Established Ways Of Tinnitus Induction In Animal Researchmentioning
confidence: 99%